A c-di-GMP binding effector STM0435 modulates flagellar motility and pathogenicity in Salmonella - Yuanji Dai; Ruirui Liu; Yingying Yue; Nannan Song; Haihong Jia; Zhongrui Ma; Xueyan Gao; Min Zhang; Xilu Yuan; Qing Liu; Xiaoyu Liu; Bingqing Li; et al. (Virulence, 2024)
ABSTRACTFlagella play a crucial role in the invasion process of Salmonella and function as a significant antigen that triggers host pyroptosis. Regulation of flagellar biogenesis is essential for both pathogenicity and immune escape of Salmonella. We identified the conserved and unknown function protein STM0435 as a new flagellar regulator. The ∆stm0435 strain exhibited higher pathogenicity in both cellular and animal infection experiments than the wild-type Salmonella. Proteomic and transcriptomic analyses demonstrated dramatic increases in almost all flagellar genes in the ∆stm0435 strain compared to wild-type Salmonella. In a surface plasmon resonance assay, purified STM0435 protein-bound c-di-GMP had an affinity of ~8.383 µM. The crystal structures of apo-STM0435 and STM0435&c-di-GMP complex were determined. Structural analysis revealed that R33, R137, and D138 of STM0435 were essential for c-di-GMP binding. A Salmonella with STM1987 (GGDEF protein) or STM4264 (EAL protein) overexpression exhibits completely different motility behaviours, indicating that the binding of c-di-GMP to STM0435 promotes its inhibitory effect on Salmonella flagellar biogenesis.